A Note on Nonlinear Biharmonic Equations with Negative Exponents - Guerra-Benavente, I (2012)
In this paper we study radially symmetric entire solutions of ? 2u=-u -q,u>0 in R3. We find the asymptotic behavior of these solutions for any q> 1 and prove that for any q> 3 there exists a solution with exactly linear growth. © 2012 Elsevier Inc.